CARDIAC ARRHYTHMIAS IN PATIENTS CIRRHOSIS OF THE LIVER - Aripov Shakar Maxmudovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Cirrhosis of the liver (CP) is one of the urgent problems of medicine of the last decade. This is due to a large increase in viral liver diseases, especially caused by hepatitis B and C viruses. The CPU is characterized by hyperdynamic blood circulation, which manifests itself in the form of visceral vasodilation and increased cardiac output. These violations of the system circulations in combination with high intrahepatic resistance contribute to the development and progression of portal hypertension and often represent the main complications of cirrhosis in the form of varicose bleeding and ascites. The possibility of associated specific myocardial disorders in liver cirrhosis has been recognized relatively recently. These disorders include enlargement of the left ventricular cavity associated with its diastolic dysfunction and systolic incompetence during exercise. The combination of such violations is typical for the so-called cirrhotic cardiomyopathy . Meanwhile, the syndrome of cirrhotic cardiomyopathy has not yet been definitively classified and many mechanisms for the development of myocardial dysfunction in patients with CP are unknown. The absence of these data indicates insufficient awareness of practitioners about changes in the cardiovascular system in patients with cirrhosis of the liver. Early diagnosis and clinical intervention may possibly improve the survival of these patients. In patients with cirrhosis of the liver of viral etiology, an increase in the volume of the left atrium, a violation of rhythm and conduction, prolongation of the QT interval, a decrease in heart rate variability, global longitudinal systolic ventricular function, a violation of segmental diastolic ventricular function was found. These changes are more pronounced in patients with ascites